Validation and utility study of the 10 item brief adult health capital scale (BACHS-10). (February 2022) - Hanauer, Matthew; Svetina Valdivia, Dubravka
Current methods for assessing health capital are not accessible to clinicians. To increase accessibility, we evaluated a Brief Adult Health Capital Scale (BAHCS-10) using classical and modern testing theories. With 588 clients, we found an adequate fit for the BAHCS-10χ s c a l e d 2 ( 35 ) = 97 . 19, p < . 01, CFIscaled = 0.949, TLIscaled = 0.935, RMSEA = 0.077, and the SRMR = 0.060. We also found evidence of invariance across race but did find significant non-invariance across some items for gender and age. Future researchers should review items displaying noninvariance and develop optimal cut scores for the BAHCS-10 to further support clinician decision making.